Pengaruh Social Media Marketing, Electronic Word Of Mouth, dan Trend Fashion terhadap Minat Beli Produk Sepatu Converse (Studi Kasus Pada Mahasiswa Universitas Islam Malang) - Oktrivan Bramantya Ilham; Budi Wahono; Mohamad Bastomi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to analyze people's buying interest in Converse shoes based on the marketing strategy carried out by Converse on social media, information circulating on internet media related to Converse shoes shared by other users, and clothing styles that are currently a trend in society. This type of research is Explanatory Research using quantitative methods. The population is students of the Islamic University of Malang with a sample of 100 respondents along with a sampling technique, namely Purposive Sampling. The data source comes from primary data by distributing questionnaires and using SPSS version 25.0 as a data analysis tool. The test results show simultaneously and partially that Social Media Marketing (X1), Electronic Word Of Mouth (X2), and Fashion Trends (X3) have a positive effect on Purchase Intention (Y). Kata Kunci: Social Media Marketing, Electronic Word Of Mouth, Trend Fashion, Sepatu Converse.